Correlated strength enhancement mechanisms in carbon nanotube based geopolymer and OPC binders. (25th October 2021) - Azeem, Muhammad; Junaid, M. Talha; Saleem, Muhammad Azhar
Highlights: The CNTs in the OPC and geopolymer binders enhances the compressive and the flexural strengths. The crystals in the binders grow at the CNT sites. The CNTs increase the entropy of the composite material systems. There is electrostatic interaction between the composite materials and the CNTs. The surface defects of the CNTs enhance the ion–dipole interaction. Abstract: The environmental impact of the cement industry can be controlled by substituting a part of the cement with supplementary cementitious materials such as carbon nanotubes (CNTs). The CNTs alter the physical and mechanical properties of the binders. However, a poor understanding of their strength enhancing mechanism in the binders obstructs their industrial applications. This report reveals a correlation between improved compressive strengths of the ordinary Portland cement (OPC) and geopolymer matrices with CNTs indicating that the strength enhancing mechanism in both the binders must be the same. Based on the XRD, FTIR and SEM/EDS measurements, there are strong indications that the structural and morphological defects in the CNTs facilitate an ion–dipole interaction with the compounds of the binders. This facilitates the growth of the large crystallites in the matrix resulting into a compressive strength increased by 21% to 24%. 1